October 7 and International Police Cooperation: The Silence of Interpol (Belügyi Szemle, 2025)
Aim: The aim of this study is to explore the background and interpretation of Interpol’s silence following the terrorist attacks committed by Hamas against Israel on October 7, 2023. The author examines the international policing implications of the events, with special attention to why the world’s largest police organization failed to issue any substantive response.Methodology: The research is based on a sociological analysis combining a historical and institutional overview of Interpol’s counterterrorism activities with the examination of the organization’s communications and institutional decisions. It relies on qualitative sources and an interpretive, case study-based approach using public documents, records, and statements.Findings: The study finds that Interpol has gradually retreated from actively addressing terrorism over the past decade, and that its complete silence regarding the October 7, 2023 attacks is particularly striking. This inaction not only contrasts with the organization’s earlier practices, but also raises questions about political pressure, professional autonomy, and the integrity of the organization’s neutrality.Value: The study contributes to a better understanding of the political and institutional characteristics of international police cooperation and offers new perspectives for critically evaluating Interpol’s role in the global fight against terrorism. The author highlights that the organization’s apparent neutrality often conceals underlying political and geopolitical considerations.